Proximate Analysis and Multifunctional Roles of C. cyminum (Zeera) Extract for Investigating the Frontier of Hypolipidemic and Anti-Obesity Efficacy in Women - Akmal, Amna; Farooq, Al Ayesha; Anwar, Shakila; Ajmal, Muntaha; Fatima, Noor; Nazakat, Janees; Khan, Daniya Muzammil; Javed, Laiba; Zafar, Imran; Shafiq, Shaista (Indus Journal of Bioscience Research, 2025)
This study examines the impact of C. cyminum (Zeera) powder intervention on various health parameters, including proximate analysis, lipid profile assessment, and anthropometric measurements. Proximate analysis revealed moisture (7.56±0.55%), protein (19.22±0.1%), fat (23.3±0.6%), crude fiber (11.43±0.4%), ash (7.08±0.08%), and nitrogen-free extract (30.55±0.29% mg/dL). Lipid profile analysis post-intervention demonstrated significant improvements: total cholesterol decreased from 168.67±2.58 to 150.47±4.55, LDL from 96.80±1.52 to 78.87±1.34, HDL increased from 44.40±1.74 to 55.47±0.94, and triglycerides decreased from 170.67±8.83 to 149.40±6.74. Statistical analyses revealed significant effects of treatment on lipid profiles (p < 0.01). Anthropometric measurements taken post-intervention revealed substantial weight loss (p < 0.001), a reduced BMI (p < 0.001), and a decreased waist circumference (p < 0.001). Additionally, the waist-to-hip ratio significantly declined (p < 0.001), along with a noteworthy decrease in mid-arm circumference (p < 0.01). These findings suggest the potential of C. cyminum powder as a non-pharmacological intervention for improving lipid profiles and promoting weight loss. However, further research is warranted to explore the long-term sustainability and generalizability of these findings across diverse populations.